Cover Image. Issue 7 (11th September 2020) - Vince, Nicolas; Douillard, Venceslas; Geffard, Estelle; Meyer, Diogo; Castelli, Erick C.; Mack, Steven J.; Limou, Sophie; Gourraud, Pierre‐Antoine
Abstract : Front Cover Caption: The cover image is based on the Original Article SNP‐HLA Reference Consortium (SHLARC): HLA and SNP data sharing for promoting MHC‐centric analyses in genomics by Nicolas Vince et al., https://doi.org/10.1002/gepi.22334 .